L'art solutréen du Roc de Sers (Charente) - Tymula, Sophie (Documents d'archéologie française, 2002)
Of fundamental importance for the study of palaeolithic art, the Solutrean settlement site of Roc de Sers and the sculpted cave-wall art which typihes it are presented within a rigorous scientific framework Beyond the form-support relationship, developed to its fullest expression in the Magdalenian period, and the canon of gestures resulting from carefully controlled transmission of technical sculpting procedures, artistic and symbolic expression, seen from a techno-economic and sociocultural perspective, were enhanced by other inventive innovations Complex construction, use of contours and mastery of shadow work together to create Visual effects suggesting volume and perspective. The mastery of the third dimension, a considerable advance in the realm of cave-wall art, combines figurative art with unconventional, sometimes abstract composite figures, reflecting a society in which the concept of regionalism is gaining ground.